Peranan Berbagai Pola Agroforestri Terhadap Tingkat Resiliensi Petani Di SUB DAS Minraleng Hulu - A. Azhar Armas; Muh Dassir; Syamsuddin Millang (Fakultas Kehutanan, Universitas Hasanuddin, 2020)
Abstract. This research wants to see the roles of various agroforestry patterns and the level of resilience of farmers in facing crisis/ekstreme conditions and how it affects farmers household income.This study aims to (1) describe the patterns of agroforestry applied by farmers, (2) Determine factors that influence resilience, (3) Analyze the level of resilience in various agroforestry patterns in the Upper Minraleng Upper watershed. Qualitative and quantitative analysis ware carried out on farmers in various agroforestry patterns and supported by research respondent information for each agroforestry pattern, 30 respondents were selected so that the total of respondens was 90 farmer household respondents. The results of the study shows that the agroforestry pattern applied by farmers in the Upper Minraleng Sub-watershed is dominanted by teak, candlenut and acacia agroforestry patterns, in which all three patterns are managed in the form of agrisilviculture. Factors affecting resilience in various agroforestry patterns of farmers are the time of recovery at a critical time and the level of adaptation at a critical time. In addition, the highest resilience level is candlenut-dominanted agroforestry pattern farmers with a total score of 1970, moderate resilience level in teak-dominanted agroforestry patterns with a total score of 1844 and the lowest agroforestry level in teak dominated agroforestry patterns with a total score of 1634. Keywords: Agroforestry, Resilience, Resilience of Level